Sanksi Pidana Kerja Sosial terhadap Pengguna Knalpot Racing Sepeda Motor - Nurhasan Nurhasan (Wajah Hukum, 2022)
The existence of exhaust racing is currently very troubling to the community so that sanctions are needed in accordance with the actions committed by the violator. The type of research used in this research is normative juridical so that this research is more descriptive in nature, the data sources are primary, secondary and tertiary sources, then the research approach this is a statutory approach, the data collection technique in this research is a document study and the data analysis in this research is carried out qualitatively. The results show that the regulation of criminal sanctions against motorcycle racing exhaust users in Law Number 22 of 2009 concerning Road Traffic and Transportation is regulated in Article 285 paragraph (1) of Law Number 22 of 2009 concerning Road Traffic and Transportation. Then the impact of motorcycle racing exhaust users is that it can pollute the air and cause noise pollution. For perpetrators of violations of motorcycle racing exhaust users, the sanctions imposed include bringing the racing exhaust closer to the ears of the motorcycle racing exhaust user, doing push-ups and the like which can be categorized as sports and sweeping on the roadside, assisting the environmental cleaning service to clean the city and others.